Cancer incidence in the cohort exposed to Cesium-137 accident in Goiânia (Brazil) in 1987 - Curado, Maria Paula; Oliveira, Max Moura de; Valverde, Nelson Dias; Cruz, Aparecido Divino da (Journal of Health & Biological Sciences, 2019)
Objective:to describe the incidence of cancer cases in the direct victims of the accident, Groups I and II, and compare with overall cancer incidence rates for the population of Goiânia. Method: A descriptive study is presented herein, on the cohort of patients directly exposed and contaminated (Groups I and II) during the cesium-137 accident, which occurred in Goiania (Midwest Brazil) in 1987. The incident cases of malignant neoplasms diagnosed between 1988 and 2017 are described. Analysis included calculation of the Incidence Rate Ratio (IRR) with 95% confidence intervals (CI95%), according to gender. Results: In the 30-year period (1987-2017) following individual exposure, there were seven cancer cases in six directly exposed victims of the cesium-137 accident. Of these, five neoplasms occurred in men, in the esophagus (1), prostrate (3), bladder (1), and two in women, involving breast cancer (1) and skin melanoma (1). The accumulated incidence rates in the direct victims of the Cesium-137 accident were 327.9/100,000 for men and 148.6/100,000 for women. For the overall population of Goiânia, rates were 221.4/100,000 and 231.2/100,000 in men and women, respectively. The ratios of brute incidence rates (direct victims of Cesium-137/population of Goiânia) were 1.5 (IC95%:0.4;5.9) in men and 0.6 (IC95%:0.1;3.8) in women, with no statistically significant differences. Conclusion: Cancer incidence in the direct victims of the Cesium-137 accident (Groups I and II), according to sex, was not different from the incidence in those not exposed to Cesium-137 in the municipality of Goiânia. Cancer risk was similar to that of the general population of the municipality of Goiânia